Registration of Five Upland Cotton Mutant Germplasm Lines with Superior Fiber Length, Strength, and Uniformity. Issue 1 (26th October 2017) - Bechere, Efrem; Zeng, Linghe; Auld, Dick
Abstract : Mutant germplasm lines MD 15‐Mut 13 (Reg. No. GP‐1025, PI 681706), MD 15‐Mut 31 (Reg. No. GP‐1026, PI 681707), MD 15‐Mut 61 (Reg. No. GP‐1027, PI 681708), MD 15‐Mut 89 (Reg. No. GP‐1028, PI 681709), and MD 15‐Mut 138 (Reg. No. GP‐1029, PI 681710) are unique genotypes of upland cotton ( Gossypium hirsutum L.). These germplasm lines were developed by the USDA‐ARS, Stoneville, MS, and released on 18 Apr. 2017. In 2008, about 5000 seeds of the germplasm line MD 15 were chemically mutagenized with 3.2% (v/v) of ethyl methane sulfonate. The treated seeds were hand planted in the field in 2008 to produce the M0 generation. One boll was hand‐picked from each of 2000 surviving plants, and this bulk was planted in 2009 to produce the M1 . In 2010, 2011, and 2012, the same procedure was followed to produce the M2, M3, and M4 generations, respectively. Individual progeny rows of the best fiber quality mutants, along with the check genotypes, were tested in replicated trials at Stoneville during 2013 to 2016. These tests identified five mutants designated as MD 15‐Mut 13, MD 15‐Mut 31, MD 15‐Mut 61, MD 15‐Mut 89 and MD 15‐Mut 138 with outstanding fiber length, strength, and uniformity. These mutants have long to extra‐long, very strong, and highly uniform fibers.